2011
DOI: 10.1002/jsfa.4473
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze glycoprotein agents: structural requirements for activity

Abstract: Antifreeze glycoproteins (AFGPs) are considered to be the most efficient means to reduce ice damage to cell tissues since they are able to inhibit growth and crystallization of ice. The key element of antifreeze proteins is to act in a non-colligative manner which allows them to function at concentrations 300-500 times lowers than other dissolved solutes. During the past decade, AFGPs have demonstrated tremendous potential for many pharmaceutical and food applications. Presently, the only route to obtain AFGPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Each spectrum was obtained as an average of three scans taken at a rate of 20 (nm/min) with a spectral band of 1nm. Each experiment was repeated four times and averages were taken of the resulting data …”
Section: Methodsmentioning
confidence: 99%
“…Each spectrum was obtained as an average of three scans taken at a rate of 20 (nm/min) with a spectral band of 1nm. Each experiment was repeated four times and averages were taken of the resulting data …”
Section: Methodsmentioning
confidence: 99%
“…The interaction between antifreeze proteins (AFPs) and water has intrigued many researchers, particularly to elucidate the mechanisms whereby the AFP inhibits the formation of ice crystals (Carvajal-Rondanelli, Marshall, & Guzman, 2011;Matsumoto, Saito, & Ohmine, 2002;Petzold & Aguilera, 2009). MD simulations on AFP indicated that the solvation water around the protein molecule preconfigured the ice-binding face.…”
Section: Effects Of Water and Salts On Proteins Carbohydrates And Lmentioning
confidence: 99%
“…Additional properties of AFPs include the inhibition of ice recrystallization or cell membrane stabilization at low temperatures (Davies and Sykes, 1997, Venketesh and Dayananda, 2008). Antifreeze glycoproteins (AFGPs), a class of AFPs, are characterized by canonical Ala-Ala-Thr or Pro-Ala-Thr repeats with a β-D-galactosyl-(1→3)-α-N-acetyl-D-galactosamine disaccharide attached to each threonine (Carvajal-Rondanelli et al, 2011). Arctic fish AFGPs contain between 4 to 55 repeats, and AFGPs of different length may synergize, suggesting functional differences encoded into the number of tripeptide repeats and spacer sequences between them (Garner and Harding, 2010).…”
Section: Introductionmentioning
confidence: 99%